(untitled) (Journal of Comparative & International Higher Education, 2021)
The purpose of this study was to determine the difficulties and expectations of foreign nursing students during their nursing practice in the clinic. This qualitative study was conducted with six foreign students studying in the department of nursing at a university in Turkey. The data were collected by using a focus group interview method, and two focus group interviews were held. Two main themes, namely, difficulties during the nursing practices in the clinic and expectations, and related subthemes were determined. All the students described the difficulties they experienced regarding nursing practices in the hospital. The foreign and migrant students participating in this study experienced difficulties regarding communication, applying treatments, providing training to patients, and applying care interventions to patients during nursing practice in the clinic; they also had expectations from nursing educators to spend sufficient time with them and be present with them in the clinic, and from nurses to assist them for adaptation to the clinic.